Reference Interval for Pulse Oxygen Saturation in Neonates at Different Altitudes: A Systematic Review - Wang, Bo; Zhang, Jia; Wu, Ya-Zhen; Lu, Zhi-Hui; Wang, Na; Yu, Zhang-Bin (Frontiers in Pediatrics, 2021)
Introduction: The reference interval for pulse oxygen saturation (SpO2) in neonates born at high altitudes has not been defined to date. The purpose of this study was to systematically review published studies and determine the reference interval of SpO2 in neonates at different altitudes. Methods: Databases of PubMed, Embase, Cochrane Library, Clinicaltrials.Gov, Chinese National Knowledge Infrastructure Database, Wanfang Database, Chinese Science Technology Journals Database, and Chinese Clinical Trial Registry were searched for studies reporting SpO2 in healthy neonates at different altitudes. Retrieval time was from inception of the database to August 16, 2021. The Agency for Healthcare Research and Quality checklist was used to evaluate the quality of studies. Python v3.8 was used to analyze the data. This systematic review was drafted in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: Seven cross-sectional studies, published between 1991 and 2020, were identified. They were from US, Mexico, Israel, Ecuador, and China. Three studies were rated as high quality and four as moderate quality. The mean SpO2 (with standard deviation or standard error) of neonates born in 40 different altitudes (ranging from 25 meters to 3,100 meters) were obtained. The prediction equation for calculation of the lower limit of the reference interval was established, and the reference intervals for SpO2 at different altitudes were determined. Conclusions: In healthy neonates, the lower limit of the reference interval of SpO2 decreases with increase in altitude. High-quality prospective studies are need to confirm our findings.